2011
DOI: 10.1063/1.3669491
|View full text |Cite
|
Sign up to set email alerts
|

Weak d magnetism in C and N doped ZnO

Abstract: We present an ab initio study of carbon and nitrogen substituting oxygen in zinc oxide structure. Detailed spin-polarized total-energy calculations of the various defect and dopant at different charge states and geometries indicate a non-zero spin magnetic moment only found from the CO-2 while NO shows no sign of localized magnetic moment. It is also revealed that CO has a tendency towards forming C2 complexes inside the ZnO structure with very weak antiferromagnetic spin arrangement. Furthermore, it was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…This emphasizes the role of cation vacancies at the GBs in promoting the FM observed in TM or RE-doped ZnO. [11][12][13][14][15] To further investigate the possibility of RT ferromagnetic coupling originating from the GB, we calculate the energy difference (∆E) between the ferromagnetic and antiferromagnetic (AFM) states for the two vacancy configurations and shown in Table II. The exchange coupling energy difference between the two vacancies (V Zn1 and V Zn2 ) is defined as where the arrows represent spin-up and spin-down states, respectively.…”
Section: B Magnetismmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the role of cation vacancies at the GBs in promoting the FM observed in TM or RE-doped ZnO. [11][12][13][14][15] To further investigate the possibility of RT ferromagnetic coupling originating from the GB, we calculate the energy difference (∆E) between the ferromagnetic and antiferromagnetic (AFM) states for the two vacancy configurations and shown in Table II. The exchange coupling energy difference between the two vacancies (V Zn1 and V Zn2 ) is defined as where the arrows represent spin-up and spin-down states, respectively.…”
Section: B Magnetismmentioning
confidence: 99%
“…Since these localized holes are located in the p-band, rather than in the d-band, this phenomenon is referred to as d 0 FM. [11][12][13][14] It has been proven to be an alternative to TM doping, as the magnetization originates in the presence of sufficient holes. However, the formation energy (E f ) of cation vacancy in bulk ZnO is high, making the achievement of FM difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al, in a comparative study with Ne implanted ZnO, show that the RTFM observed in C implanted ZnO is due to the chemical involvement of the C ions. Ab initio Density Functional Theory (DFT) study of Pham et al [19] yield the result that the dominant state of C in ZnO is C in the O-vacancy where it is in the 2− charge state, i.e. C 2− O .…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] This leads to the magnetism in nanostructures which needs to be controlled by tuning the defects in the host lattice. Pham et al 24 have reported the evolution of RTFM due to the substitution of N at O site in Zn-O nanostructure on the basis of ab initio study of spin-polarized total energy of various defects and nonmagnetic dopants having different charge states. They concluded that when N replaces O, it shortens the bond length of Zn-N due to the difference in N and O ionic radii.…”
Section: Introductionmentioning
confidence: 99%